Medical microbiology - NA. ([S.l.] : Churchill Livingstone, 2012)
About the book: medical microbiology, international edition building on the huge success of previous editions, medical microbiology 18/e will inform and inspire a new generation of readers. Now fully revised and updated, initial sections cover the basic biology of microbes, infection and immunity and are followed by a systematic review of infective agents, their associated diseases and their control. A final integrating section addresses the essential principles of diagnosis, treatment and management. An unrivalled collection of international contributors continues to ensure the relevance of the book worldwide and complementary access to the complete online version on student consult further enhances the learning experience.
Keywords: medical,micribiology